2014
DOI: 10.1155/2014/802473
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide Induced Delayed Persistent Hypercalcemia

Abstract: Teriparatide, a recombinant PTH, is an anabolic treatment for osteoporosis that increases bone density. Transient hypercalcemia is a reported side effect of teriparatide that is seen few hours following administration of teriparatide and resolves usually within 16 hours of drug administration. Persistent hypercalcemia, although not observed in clinical trials, is rarely reported. The current case describes a rare complication of teriparatide induced delayed persistent hypercalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Observations related to transitory hypercalcemia: In our cohort, 16.6% of patients were registered with temporary increase of blood calcium in a drug-related manner, a rate that confirms data from literature [12][13][14][15]. In neither of cases with transitor y hypercalcemia TPT was not necessary to be stopped.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Observations related to transitory hypercalcemia: In our cohort, 16.6% of patients were registered with temporary increase of blood calcium in a drug-related manner, a rate that confirms data from literature [12][13][14][15]. In neither of cases with transitor y hypercalcemia TPT was not necessary to be stopped.…”
Section: Resultssupporting
confidence: 88%
“…In the meantime the calcium evaluation is useful but some transitory self-limited cases of hypercalcemia may not be detected if a specific calendar of serum calcium assessment is not similarly performed in each case. Moreover, the timing of blood calcium assay is important since most of TPT-related hypercalcemia cases are described within first 16 hours of administration [12][13][14][15]. In our study all included patients were confirmed with hypercalcemia for at least two different assays in two different days.…”
Section: Resultsmentioning
confidence: 99%
“… 12 Those admitted were treated with intravenous fluids, diuretics and/or intravenous bisphosphonates. 13 16 Sustained hypercalcemia persisting for a week after teriparatide discontinuation has been reported as well. 14 In three patients, PTH was measured during the hypercalcemic episode.…”
Section: Discussionmentioning
confidence: 92%
“…On the lymphoma spectrum, those with non-Hodgkin's lymphoma [35], chronic myeloid leukemia (blast phase) [6], and adult T-cell leukemia-lymphoma may have PTHrP-induced hypercalcemia [7, 8]. Teriparatide administration was unlikely because the effects of hypercalcemia are transient, usually resolving sixteen hours after the last administration [9]. Milk-alkali syndrome was unlikely given that she reported the consumption of only six tablets over a span of a month.…”
Section: Differential Diagnosismentioning
confidence: 99%